Penerapan Model Rapid Application Development Pada Perancangan Sistem Informasi Jasa Pengiriman Barang - Lala Nilawati; Dedeh Sulastri; Yuyun Yuningsih (Paradigma, 2020)
Freight forwarding company is a company or business entity which is engaged in providing freight forwarding services. In connection with business activities that occur in service companies, a good management information system is needed that can manage data delivery. The availability of a good and accurate information system will be increasingly needed along with the increasing human need for information that is fast, precise and accurate. The steps needed to produce a software system so that it has good performance, of course, can not be separated from how to choose and apply the analysis and design methods. In this research, a goods delivery system will be designed using Rapid Application Development (RAD), where the authors analyze the data management system contained in the company, then create a prototype design that is suitable for data management to make it more complete, efficient, and easy to use as a development from the old system using Java Script and MySQL as its database. In addition, in designing the proposed system, which is the information system of freight forwarding services, the tools used are using ERD (Entity Relationship Diagram) and UML (Unified Modeling Language). Based on the analysis and application of the system followed by testing the system, the delivery system designed can make it easier for system users to process data, control data and prepare reports related to shipping data.